2023
DOI: 10.1155/2023/4717110
|View full text |Cite
|
Sign up to set email alerts
|

Application of Deep Learning to the Prediction of Solar Irradiance through Missing Data

R. Girimurugan,
P. Selvaraju,
Prabahar Jeevanandam
et al.

Abstract: The task of predicting solar irradiance is critical in the development of renewable energy sources. This research is aimed at predicting the photovoltaic plant’s irradiance or power and serving as a standard for grid stability. In practical situations, missing data can drastically diminish prediction precision. Meanwhile, it is tough to pick an appropriate imputation approach before modeling because of not knowing the distribution of datasets. Furthermore, not all datasets benefit equally from using the same i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…This observation gives the exact comparison of using thermal storage unit with the single slope solar still integrated with the PSC. The productivity of this experiment gives almost 61% [3]. The DSSD coupled with relatively sun warmed solar pond (Shallow) showed the improved productivity than the others.…”
Section: Introductionmentioning
confidence: 72%
“…This observation gives the exact comparison of using thermal storage unit with the single slope solar still integrated with the PSC. The productivity of this experiment gives almost 61% [3]. The DSSD coupled with relatively sun warmed solar pond (Shallow) showed the improved productivity than the others.…”
Section: Introductionmentioning
confidence: 72%
“…Kim, T. et al [25] proposed the impact of missing weather information on PV forecasting performance was analyzed by applying imputation methods such as LI and MICE before developing the forecasting model, wherein the KNN-applied model outperformed other imputation-applied models. Girimurugan, R. et al [26] proposed an adaptive neural imputation module (ANIM) coupled with a recurrent neural network (RNN) and an attention imputed gate recurrent unit (AIGRU), which effectively utilizes the distribution of each weather variable during the imputation process, surpassing traditional methods like KNN in efficacy. Lastly, Lee, D. S. et al [27] devised a two-stage approach employing linear regression and KNN to address missing weather data in the development of short-and medium-term PV forecasting models, which yielded enhanced performance compared to models that did not incorporate these imputation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have primarily focused on developing forecasting models and evaluating their performance after imputing missing PV data [24][25][26][27]. Our review identified that different forecasting performances emerged when single imputation methods were applied to PV data, influenced by the characteristics of the imputation method and weather conditions.…”
Section: Introductionmentioning
confidence: 99%